3D Electron Diffraction Unravels the New Zeolite ECNU‐23 from the "Pure" Powder Sample of ECNU‐21. Issue 3 (27th November 2019) - Liu, Xue; Luo, Yi; Mao, Wenting; Jiang, Jingang; Xu, Hao; Han, Lu; Sun, Junliang; Wu, Peng
Abstract: A novel crystalline high‐silica zeolite with 12×8‐membered ring (R) channel system is prepared with the aid of the 3D electron diffraction (3D ED) technique. A crystal with the same topology as one of the predicted daughter structures of CIT‐13 germanosilicate, named ECNU‐23 (East China Normal University 23) was coincidentally detected by the 3D ED investigation during the structure characterization of the "pure" powder sample of existing one‐dimension (1D) 10‐R ECNU‐21. By controlling the alkaline‐assisted hydrolysis under moderate conditions, we purified the phase of ECNU‐23 by selectively breaking and removing the chemically weak Ge(Si)‐O‐Ge and metastable Si‐O‐Si bonds. Its structure was determined based on the 3D ED data, and confirmed by high‐resolution TEM images and powder X‐ray diffraction (PXRD) data. The aluminosilicate Al‐ECNU‐23 shows unique catalytic properties in the isomerization/ disproportionation of m ‐xylene as solid‐acid catalyst. Abstract : Use your ED : A new high‐crystalline zeolite, ECNU‐23, has been prepared with the assistance of the 3D electron‐diffraction (ED) technique. The aluminosilicate Al‐ECNU‐23 shows unique catalytic properties in the isomerization/ disproportionation of m ‐xylene as solid‐acid catalyst.